2019
DOI: 10.2166/aqua.2019.032
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of using different lining materials to protect groundwater from leakage of polluted streams

Abstract: Groundwater is one of the most important water sources but it is often not far away from pollution. One source of pollution is leakage from polluted streams such as open drains. The effect of open drains on groundwater quality has become an essential issue. This study aims to use different lining materials to minimize the seepage from open drains to protect groundwater. MODFLOW is used to investigate flow and contaminant transport and to evaluate efficiency of different lining materials. A hypothetical case st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…Abd-Elhamid et al [ 22 ] developed a numerical model to evaluate efficiency of lining materials for open polluted drains including clay, bentonite, geomembranes, and concrete to reach 43, 89.6, 91.4, and 93% compared with the base case. Additionally, the result showed that the geomembranes high performance for groundwater protection compare with these materials due to high durability and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…Abd-Elhamid et al [ 22 ] developed a numerical model to evaluate efficiency of lining materials for open polluted drains including clay, bentonite, geomembranes, and concrete to reach 43, 89.6, 91.4, and 93% compared with the base case. Additionally, the result showed that the geomembranes high performance for groundwater protection compare with these materials due to high durability and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…Layer need to be placed below the area of the remediated soil (by excavating) to limit/block the percolation of water that carries soluble metal ion (Adar and Bilgili, 2015). Several layer types can be used on the application, including geomembrane and clay (Abd-Elhamid et al, 2019).…”
Section: Analysis Of Al Content In Soilmentioning
confidence: 99%
“…The sediments constitute variable proportions of sands, clays, and gravels with lateral and vertical variation. Such sediments rest uncomfortably on the older units of Tertiary [ 19 ] Pleistocene (old deltaic deposits are classified to Early, Middle and Late Pleistocene). Early Pleistocene deposits are represented by loose sands with cherty pebbles.…”
Section: Geologic Settingmentioning
confidence: 99%